Verify the identity. cot(2x) = sin x + sin(3x) / cos x - cos(3x)
- print Print
- list Cite
Expert Answers
calendarEducator since 2011
write5,348 answers
starTop subjects are Math, Science, and Business
Use this formula for the numerator sin x + sin 3x.
sin p + sin q = 2 sin ((p+q)/2)*cos ((p-q)/2)
sin x + sin 3x = 2 sin ((x+3x)/2)*cos ((x-3x)/2)
sin x + sin 3x = 2 sin (2x)*cos(-2x)
The cosine function is even, therefore cos(-2x) = cos 2x
sin x + sin 3x = 2 sin (2x)*cos(2x)
Use this formula for the denominator cos x - cos 3x.
cos p - cos q = -2 sin ((p+q)/2)*sin ((p-q)/2)
cos x - cos 3x = 2 sin (2x)*sin (2x)
(sin x + sin 3x)/(cos x - cos 3x) = 2 sin (2x)*cos(2x)/2 sin (2x)*sin (2x)
Reduce terms: (sin x + sin 3x)/(cos x - cos 3x) =cos(2x)/sin (2x)
(sin x + sin 3x)/(cos x - cos 3x) = cot (2x)
ANSWER: The last line proves the identity (sin x + sin 3x)/(cos x - cos 3x) = cot (2x)
Related Questions
- cos x-sin 3x-cos 2x = 0
- 1 Educator Answer
- How to verify this identity?(sin 2x / sinx) - (cos 2x / cos x) = sec x thank you!
- 1 Educator Answer
- How to prove the identity `sin^2x + cos^2x = 1` ?
- 3 Educator Answers
- Verify the identity sin^4x-cos^4x=2sin^2x-1
- 2 Educator Answers
- Verify the following identity: `tanx(cot x + tan x) = sec^2x`
- 2 Educator Answers
calendarEducator since 2011
write562 answers
starTop subjects are Math, Science, and Business
sin(A+B)= sin(A)cos(B) + cos(A)sin(B)
sin(A-B) = sin(A)cos(B) - cos(A)sin(B)
sin(A+B) + sin(A-B) = 2sin(A)cos(B)
cos(A+B) = cos(A)cos(B) - sin(A)sin(B)
cos(A-B) = cos(A)cos(B) + sin(A)sin(B)
Subtracting
cos(A-B) - cos(A+B) = 2sin(A)sin(B)
So
sin(x) + sin(3x) = sin(2x-x) + sin(2x+x) = 2sin(2x)cos(x)
cos(x) - cos(3x) = cos(2x-x) - cos(2x+x) = 2sin(2x)sin(x)
So
(2sin(2x)cos(x))/(2sin(2x)sin(x)) = cos(x)/sin(x) = cot(x)
So this identity is not true.
cos(A-B) + cos(A+B) = 2cos(A)cos(B)
cos(x) + cos(3x) = cos(2x - x) + cos(2x + x) = 2cos(2x)cos(x)
(sin(3x)+sin(x))/(cos(x)+cos(3x)) = tan(2x)
calendarEducator since 2010
write12,554 answers
starTop subjects are Math, Science, and Business
The given expression -cot(2x) = sin x + sin(3x) / cos x - cos(3x) is not an identity.
For example for x = `pi/6` .
`-cot(2*pi/6)` = -0.5773` `
On the other hand `sin(pi/6) + (sin (pi/2))/(cos (pi/6)) - cos (pi/2)`
=> 1.654
The two are not equal showing that the expression is not an identity.